Treatment of osteonecrosis of the femoral head by botulinum toxin type A injection to the psoas muscle -A case report - Kim, Sung-Yul; Lee, Dong-Hyun; Kim, Sun-Hee; Cho, Yong-Hyun (Anesthesia and pain medicine (Korean society of anesthesiologists), 2017)
Osteonecrosis of the femoral head (ONFH) can cause femoral head depression and cortical discontinuity. Treatment for ONFH remains challenging. We performed botulinum toxin type A injection to psoas major muscle in five patients with radiological femoral head collapse (Association Research Circulation Osseus classification stage III) who were non-responsive after two years of conservative treatment (tramadol 200 mg/day, mefenamic acid 1,000 mg/day). At two weeks after the procedure, their mean hip pain was decreased from 88 ± 0.4/100 mm to 22 ± 0.4/100 mm based on visual analogue scale (VAS). The pain was maintained at a minimum of 20/100 mm and a maximum of 30/100 mm in VAS for at least six weeks after the procedure. These values were mean ± SD. These patients were followed-up for 6 months. There was no exacerbation of pain from repeated (three times) botulinum toxin type A injection to the psoas major muscle. KCI Citation Count: 0